2016
DOI: 10.1159/000449102
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Case Fatality at the County Level as Contributors to Geographic Disparities in Stroke Mortality

Abstract: Background: Is the high stroke mortality in the Southeastern parts of the United States driven by differences in stroke incidence or case-fatality? This question remains unanswered. Differences in incidence would underscore the need for stroke prevention, while differences in case fatality would call for improved stroke care. Methods: Quartiles of US counties were defined by stroke mortality, and this gradient was related with stroke incidence and stroke case fatality in the Reasons for Geographic and Racial D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
(17 reference statements)
1
16
1
Order By: Relevance
“…27 The second suggested both a higher incidence and a higher case fatality contribute to the higher stroke mortality in the southeastern stroke belt. 28 Herein, we demonstrate that, like the stroke mortality in blacks, the rural disparity in stroke death is primarily attributable to higher incidence and not case fatality.…”
Section: Discussionmentioning
confidence: 66%
“…27 The second suggested both a higher incidence and a higher case fatality contribute to the higher stroke mortality in the southeastern stroke belt. 28 Herein, we demonstrate that, like the stroke mortality in blacks, the rural disparity in stroke death is primarily attributable to higher incidence and not case fatality.…”
Section: Discussionmentioning
confidence: 66%
“…Participants with low education were likely subjected to particularly severe economic circumstances with families hovering on the brink of starvation as well as dealing with barriers to employment, health and social services as a result of institutionalized racism (Dollard, 1957). There is now considerable evidence that certain geographically defined communities, particularly in the south are at greater risk for chronic illnesses including cancer, vascular diseases, stroke, increased all-cause mortality rates, reduced life expectancy, and most recently, for greater recording of dementia/AD in death certificates (Dwyer-Lindgren et al, 2016;Karp et al, 2016;Labarthe et al, 2016;Rosenberg et al, 2016;Taylor, Greenlund, McGuire, Lu, & Croft, 2017). The explanations given for these geographically defined areas of increased risk include socioeconomic disparities, access to health care, lifestyle factors such as physical inactivity and smoking, obesity-increased rates of vascular risk factors, obesity, hypertension, and diabetes (Karp et al, 2016;Labarthe et al, 2016;Rosenberg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, a higher stroke incidence was found in the southeastern United States, which has been widely acknowledged as 'the Stroke Belt' due to higher mortality of stroke in comparison with other regions. [18][19][20] Prior studies also indicated "the Stroke Belt" was a result of a significant number of rural residents, African American, residents with a higher prevalence of traditional stroke risk factors, inflammation and infection, as well as socio-economically deprived individuals. 18,19,[21][22][23] However, it should be noted that findings from western nations may not be general- ized to eastern countries since culture and social structure differ substantially.…”
Section: Comparison With Existing Researchmentioning
confidence: 99%